Digital assessment: impact on student motivation, peer learning, group dynamics - Tomar, Sarika; Arundhathi, Arundhathi; Gupta, Shikha; Sharma, Mansi (Intelektual Pustaka Media Utama, 2024)
As universities shifted to online education with the onset of the coronavirus disease 2019 (COVID-19) pandemic, both pedagogy and assessment patterns across disciplines underwent a change, with a shift towards collaborative digital assessments. In this context, using qualitative and quantitative methods for data collection from an assessment conducted for 55 students who worked in groups to create YouTube videos on pre-selected modules, our analysis reveals that this assessment tool had a significant impact on peer learning, motivation and group dynamics. Students were more motivated to learn and share their learning, and they could also successfully engage in recognising and addressing group dynamics, thereby cultivating more than just subject knowledge. This finding aligns with existing scholarship and the paper adds to research about pedagogy and assessment via digital education in the Indian context, which is still upcoming.